VALE: uma análise de indicadores de financeirização e seus impactos de gestão - Mesquita, Filipe Valadares (Universidade Federal de São Carlos, 2023)
The term financialization presents different concepts to characterize a series of empirical phenomena at different levels of analysis and one of the approaches identified corresponds to the examination of financialization from a critical approach to maximizing shareholder value. In this scenario, financialization appears as a process in which financial markets and services become more relevant than the real economy, discouraging productive investment and promoting rent-seeking behavior, thus increasing the influence of the banking-financial sector with regard to driving of economic policy. The main impacts are the increase in economic instability, the increased focus on adding value for shareholders, the emergence of institutional investors, the transfer of income from the real sector to the financial sector, the increase in inequality and wage stagnation. Although the process is typical of more developed economies, authors have argued that the financialization process is deepening in Brazil. Therefore, the present study proposes as a research question to identify, through financialization indicators, how this phenomenon has affected the management model at the VALE company. To this end, a case study was conducted collecting secondary data from the company VALE, through its reference forms published over a 10-year period, from 2010 to 2019, seeking to analyze the data found and compare them with financialization indicators found in the literature that provided the theoretical basis for the development of the analysis categories. The results found indicate that VALE is in fact a highly financialized company, especially when we take into account the dynamics adopted to maximize shareholder values.
VALE: an analysis of financialization indicators and their management impacts
Keywords: Financeirização; Shareholder Value; Empresas não financeiras; Indicadores financeiros; Financialization; Non-financial companies; Financial indicators; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO FINANCEIRA; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS